2008
DOI: 10.4161/cc.7.6.5550
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of cell cycle exit and differentiation of neuronal progenitors

Abstract: During development, co-ordinate regulation of cell cycle exit and differentiation of neuronal precursors is essential for generation of appropriate number of neurons and proper wiring of neuronal circuits. Recent studies have identified some of the molecules implicated in the regulation of these cellular events, but the complex machinery that orchestrates these processes into a coherent developmental program remains unclear. BM88/Cend1 is a neuronal protein associated in vivo with terminal neuron-generating di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 98 publications
(123 reference statements)
0
31
0
2
Order By: Relevance
“…Decelerated cell cycle progression is often linked to the commitment of cell fate determination (11,12,(33)(34)(35). Previously, cell cycle proteins of pluripotent cells were thought to control only the escape from the terminal cell cycle during differentiation, although their levels always remain in a state of flux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decelerated cell cycle progression is often linked to the commitment of cell fate determination (11,12,(33)(34)(35). Previously, cell cycle proteins of pluripotent cells were thought to control only the escape from the terminal cell cycle during differentiation, although their levels always remain in a state of flux.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the members of the let-7 family are among the most abundant miRNAs in adult brain. Such cell fate determination is a complex process and needs to be precisely coordinated with exit from cell cycle (11,12), and therefore involves crosstalk between the molecular pathways controlling proliferation and differentiation. Because let-7 miRNAs are tightly governed by Lin28a in neural stem cells, a prompt mechanism is required to respond to environmental signal and attenuate the inhibitory effect of Lin28a.…”
Section: Edited By Roger J Colbranmentioning
confidence: 99%
“…Premature disruption or delayed initiation of these developmental processes alters the number of neuronal types or subtypes produced, affects neuronal connectivity and can lead to neurological dysfunction. Over the recent years, a number of studies have shown that key regulators of cell cycle progression influence neural cell fate and differentiation and conversely, cell fate determinants and differentiation-inducing proteins regulate the cell cycle [for reviews see 1-4]. …”
Section: Introductionmentioning
confidence: 99%
“…Neurons are fully differentiated and do not divide in adults, and so they are considered in G 0 phase. The postmitotic state in neurons is maintained by p27 and p21 and sequestration of cyclin D in the cytoplasm (Politis et al 2008). Less is known about the cell cycle status of fibroblasts in humans, although they are assumed to be nondividing unless triggered to proliferate by trauma or increase in body size.…”
Section: Characterization Of the Cell Cycle In Vzv Host Cellsmentioning
confidence: 99%